(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article presents information about the role and importance of innovative technologies in the professional training of future chemistry teachers studying in the educational direction "chemistry" of higher educational institutions, their tasks, the organization of creative activity of students when using them.